Bisphenol S is present in culture media used for ART and cell culture. Issue 4 (9th January 2021) - Togola, A; Desmarchais, A; Téteau, O; Vignault, C; Maillard, V; Buron, C; Bristeau, S; Guérif, F; Binet, A; Elis, S
Abstract: STUDY QUESTION: Do plastic laboratory consumables and cell culture media used in ART contain bisphenols? SUMMARY ANSWER: The majority of human embryo culture media assessed contained bisphenol S close to the nanomolar concentration range, while no release of bisphenols by plastic consumables was detected under routine conditions. WHAT IS KNOWN ALREADY: The deleterious effect of the endocrine disruptor bisphenol A (BPA) on female fertility raised concerns regarding ART outcome. BPA was detected neither in media nor in the majority of plastic consumables used in ART; however, it might have already been replaced by its structural analogs, including bisphenol S (BPS). STUDY DESIGN, SIZE, DURATION: Seventeen plastic consumables and 18 cell culture and ART media were assessed for the presence of bisphenols. PARTICIPANTS/MATERIALS, SETTING, METHODS: Ten different bisphenols (bisphenol A, S, AF, AP, B, C, E, F, P and Z) were measured using an isotopic dilution according to an on-line solid phase extraction/liquid chromatography/mass spectrometry method. MAIN RESULTS AND THE ROLE OF CHANCE: While the plastic consumables did not release bisphenols under routine conditions, 16 of the 18 cell culture and ART media assessed contained BPS. Six media exhibited BPS concentrations higher than 1 nM and reached up to 6.7 nM (1693 ng/l). LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Further studies are required to investigate a greater number of ART media to identify less potentially harmful ones, in terms of bisphenol content. WIDER IMPLICATIONS OF THE FINDINGS: As BPS has already been reported to impair oocyte quality at nanomolar concentrations, its presence in ART media, at a similar concentration range, could contribute to a decrease in the ART success rate. Thus far, there has been no regulation of these compounds in the ART context. STUDY FUNDING/COMPETING INTERESTS: This study was financially supported by the 'Centre-Val de Loire' Region (Bemol project, APR IR 2017), INRAE, BRGM, the French National Research Agency (project ANR-18-CE34-0011-01 MAMBO) and the BioMedicine Agency (Project 18AMP006 FertiPhenol). The authors declare that they have no conflict of interest that could be perceived as prejudicing the impartiality of the reported research.